Illuminance study of lecture rooms and laboratories in an educational academic building based on the MS 1525 standard - Zainal, Muhammad Asyraf; Ghani, Sharin Ab; Chairul, Imran Sutan; Khiar, Mohd Shahril Ahmad (International Journal of Advances in Applied Sciences, 2025)
The lighting system is a crucial system in classrooms and other educational facilities such as laboratories and sports centers. Poor lighting conditions will affect the ability of the students to see clearly during classes and result in eye strain, fatigue, headache, and stress. Hence, this study aims to investigate the illuminance levels in four lecture rooms and six laboratories in the Faculty of Electrical Technology and Engineering, Universiti Teknikal Malaysia Melaka, Malaysia using DIALux evo 10.0 lighting design software. The illuminance levels determined from simulations were compared with the required illuminance levels for classrooms (300 lx) and laboratories (500 lx) stipulated in the Malaysian standards (MS) 1525-energy efficiency and use of renewable energy for non-residential buildings. Based on the results, the selected lecture rooms were overlit, whereas three of the laboratories were underlit. Suggestions were made to improve the illuminance levels of the lecture rooms and laboratories by changing the specifications of the lighting system or by making use of natural sunlight from the windows.